Skeletal and dental maxillary morphological characteristics in patients with impacted canines: systematic review and meta-analysis - Gudelevičiūtė, Ieva; Spaičytė, Nerija; Smailienė, Dalia (European journal of orthodontics, 2023)
There are a few hypotheses for the origin of palatally impacted canines (PIC). Nevertheless, the results of different studies are controversial. Considering the evidence available in the literature to determine the skeletal and dentoalveolar dimensions in patients with PIC using cone beam computed tomography (CBCT). This systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Statement. The literature search with no publication date restriction in five databases and hand searching was performed until April 2023. Data assessing the skeletal and dentoalveolar characteristics of subjects with PIC evaluated with CBCT was extracted, and the studies' quality was evaluated with the Newcastle-Ottawa Scale (NOS). Skeletal and dentoalveolar characteristics of subjects with PIC were compared with non-impacted subjects or non-impacted sides. MedCalc software was used to perform the meta-analysis. Statistical heterogeneity was assessed using the chi-square and I-square tests. The initial database search identified a total of 1153 studies. After applying the selection criteria, nine articles were included in the systematic review and meta-analysis. According to the NOS, all included articles were graded as "Good" quality. The meta-analysis showed a non-significant difference in measuring dentoalveolar height, alveolar first molar width, and basal lateral width. Controversial results were observed when evaluating both basal and alveolar first premolar widths. A significant difference was found when assessing anterior alveolar crest height and basal maxillary width. Studies demonstrated the reduction of both dentoalveolar and skeletal maxillary parameters of the patients with PIC. The meta-analysis indicated that PIC correlates to both vertical and transverse skeletal dimensions of the maxilla. However, the results remain controversial. The findings should be interpreted with caution due to different study designs and unbalanced groups in the included studies; therefore, further research is needed for more reliable conclusions. This systematic review and meta-analysis were registered in the International Prospective Register of Systematic Reviews (PROSPERO CRD42022362124).